Mutational Analysis of Colistin-Resistant Pseudomonas aeruginosa Isolates: From Genomic Background to Antibiotic Resistance - Telma De Sousa; Hsin-Yao Wang; Ting-Wei Lin; Manuela Caniça; Miguel J. N. Ramos; Daniela Santos; Catarina Silva; Sónia Saraiva; Racha Beyrouthy; Richard Bonnet; Michel Hébraud; Gilberto Igrejas; et al. (Pathogens)
This study analyzed eleven isolates of colistin-resistant Pseudomonas aeruginosa, originating from Portugal and Taiwan, which are associated with various pathologies. The results revealed significant genetic diversity among the isolates, with each exhibiting a distinct genetic profile. A prevalence of sequence type ST235 was observed, characterizing it as a high-risk clone, and serotyping indicated a predominance of type O11, associated with chronic respiratory infections in cystic fibrosis (CF) patients. The phylogenetic analysis demonstrated genetic diversity among the isolates, with distinct clades and complex evolutionary relationships. Additionally, transposable elements such as Tn3 and IS6 were identified in all isolates, highlighting their importance in the mobility of antibiotic resistance genes. An analysis of antimicrobial resistance profiles revealed pan-drug resistance in all isolates, with a high prevalence of genes conferring resistance to β-lactams and aminoglycosides. Furthermore, additional analyses revealed mutations in regulatory networks and specific loci previously implicated in colistin resistance, such as pmrA, cprS, phoO, and others, suggesting a possible contribution to the observed resistant phenotype. This study has a strong impact because it not only reveals the genetic diversity and resistance mechanisms in P. aeruginosa but also identifies mutations in regulatory genes associated with colistin resistance.